Shrinking citizenship : discursive practices that limit democratic participation in Latvian politics - Golubeva, Maria; Gould, Robert (On the boundary of two worlds, 2010)
The book, based on research results from a three-year study of parliamentary and media debates in Latvia, analyses the discourses of Latvian politicians and the media about nation, citizenship, cultural diversity, history and the nation-state. This is the.